MEDAN MEANING OF TASIKMALAYA HANDMADE CRAFTS - Aulia Afifah; Aulia, Hilwa Hamya; Elsa Sri Lunawati; Galang Diva Erlangga; Aveny Septi Astriani (Media Inovasi Pendidikan dan Publikasi, 2023)
Indonesia is known for its diverse culture. Each region in Indonesia has a culture with its own characteristics. One of the cities in Indonesia, namely Tasikmalaya, has a culture that is the identity of the city of Tasikmalaya. Therefore, researchers conducted research with the aim of describing the field of meaning of typical Tasikmalaya handicrafts with a range of meaning components and types of meaning. The method used is descriptive qualitative. This method is used because the results of this research are in the form of descriptions. The data source for this research is typical Tasikmlaya handicrafts. The data collection technique is by collecting data regarding typical Tasikmalaya handicrafts. The data was collected with stationery instruments. The semantic study used in this research is lexical semantics. This research produced six data on typical Tasikmalaya handicrafts. Each handicraft has a component meaning and type of meaning that can be differentiated in terms of material, use, color, etc. Therefore. Each typical Tasikmalaya handicraft product has its own characteristics, even though some products look the same.